Persistent Object Search and Surveillance Control With Safety Certificates for Drone Networks Based on Control Barrier Functions - Dan, Hayato; Hatanaka, Takeshi; Yamauchi , Junya; Shimizu, Takumi; Fujita, Masayuki (Frontiers in Robotics and AI, 2021)
In this paper, we address a persistent object search and surveillance mission for drone networks equipped with onboard cameras, and present a safe control strategy based on control barrier functions (CBFs). The mission for the object search and surveillance in this paper is defined with two subtasks, persistent search and object surveillance, which should be flexibly switched depending on the situation. Besides, to ensure actual persistency of the mission, we incorporate two additional specifications, safety (collision avoidance) and energy persistency (battery charging), into the mission. To rigorously describe the subtask of persistent search, we present a novel notion of $γ$-level persistent search and the performance certificate function as a candidate of a time-varying CBF. We then design a constraint-based controller by combining the performance certificate function with other CBFs that individually reflect other specifications. In order to manage conflicts among the specifications, the present controller prioritizes individual specifications in the order of safety, energy persistency, and persistent search/object surveillance. The present controller is finally demonstrated through simulation and experiments on a testbed.